Study of Thin Optical Films Properties Using High-performance Atomistic Simulation - Grigoriev, Fedor V.; Sulimov, Vladimir B.; Tikhonravov, Alexander V. (Supercomputing Frontiers and Innovations, 2024)
Full-atomistic modeling of the deposition of TiO2, SiO2 and TiO2–SiO2 films is performed using parallel calculations. The dependence of film density on the deposition angle and deposition energy is studied. Simulation of post-deposition annealing of film structures is also carried out. Mechanical stresses in TiO2–SiO2 films, arising due to differences in the properties of silicon dioxide and titanium dioxide, are calculated. It is found that the film density decreases with decreasing deposition energy and increasing deposition angle. The use of surfacing annealing leads to an increase in film thickness. In two-layer TiO2–SiO2 films, the stresses are compressive. Particular attention is paid to reducing computational costs when simulating large atomistic clusters, consisting of hundreds of thousands of atoms. Reducing the parameter that determines the calculation of the electrostatic part of interatomic energy significantly reduces the simulation time. At the same time, in this case, the accuracy of determining the electrostatic energy in the reciprocal space decreases, which should be taken into account during modeling.